Peran Digital Marketing Tiktok dan Elektronik Word of Mouth dalam Keputusan Pembelian Fashion pada Gen Z Wanita - Lina Mustika Reni; Musnaini Musnaini; Fitriaty Fitriaty (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the role of digital marketing and electronic word of mouth on fashion purchasing decisions among Gen Z women. This study is a quantitative research type. The determination of the number of samples in this study was 96 respondents with the sampling technique used was Purposive Sampling and the sampling method used was Non-Probability Sampling. The primary data used was obtained through a digital questionnaire, namely Google Form with a Likert scale. The data analysis method in this study used SPSS (Statistical Product and Service Solution) using IBM SPSS Statistics 25 For Windows software. The results of this study indicate that digital marketing and electronic word of mouth have a positive and significant effect on fashion purchasing decisions among Gen Z women.